Influence of Knowledge and Quality of Electronic Information System on Documentation Nursing Care with Perceived Usefulness as a Mediation Variable in the Inpatient Installation of X Hospital - Yaputra, Steven Kristianto; Wahidi, Kemala Rita; Nofierni, Nofierni (Sean Institute, 2025)
Hospitals have a role in providing complete health services. Nursing personnel have a large proportion, almost 50% of all hospital human resources. The purpose of this research is to determine the analysis of the influence of knowledge and quality of electronic information systems on nursing care documentation and perceived usefulness as a mediating variable for nursing staff in the X Hospital inpatient setting. The method used in this research is research using Structural Equation Modeling (SEM) data analysis techniques using SmartPLS version 3 software. Data collection used a survey method by taking questionnaires from 95 nurses in the X Hospital inpatient unit. The sampling technique used in this research is total sampling. The results of this research are that knowledge has a direct effect and significant to perceived usefulness. Knowledge has a direct and significant impact on nursing care documentation. Electronic information systems have a direct and significant effect on perceived usefulness. Electronic information systems have a direct and significant impact on nursing care documentation. Nursing care documentation has a direct and significant effect on perceived usefulness. Knowledge influences nursing care documentation through perceived usefulness. Electronic information systems influence nursing care documentation through perceived usefulness.